Análisis del sistema de control interno con base a los cinco elementos definido por el informe Coso II en las administradoras del Régimen Subsidiado en Colombia. (2013)
Analyze the smooth running of the activities within an organization, represents a key aspect to ensure that it can achieve its objectives and goals. This is vitally important that the company apply efficient internal control systems that allow protect their resources against waste, fraud or misuse. Note that the subsidized health insurance companies handle a considerable volume of transactions that need to be controlled through pre-established rules and procedures. Taking the example of health Asmet EPSS, is a private entity, non-profit organization, recognized by legal status, which meets the parameters of operation of a health promoter subsidized.